Governing climate change: lessons from other governance regimes - Arunabha Ghosh; Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2009)
At the heart of the existing climate change regime is a divide between developed and developing countries. The UN Framework Convention on Climate Change (UN-FCCC) enshrines "common but differentiated responsibilities and respective capabilities" and in so doing recognizes that historical responsibility for climate change rests with developed countries and that they have greater capacity to address the problem. That said, the Convention specifies no timetable for the introduction of binding commitments on developing countries, nor any agreed procedures for "graduating" countries from developing to developed status. As a result, progress in governing climate change rests heavily on finding a North-South agreement. That, in turn, rests on overcoming what Joanna Depledge and Farhana Yamin (2009) describe as "the persistence of dysfunctional North-South politics . . . negotiations between the groups tend to be dominated by kneejerk suspicion, defensiveness, and misunderstanding, which hinder the rational discussion of proposals". An "integrated multi-track approach" has been proposed by Bodansky and Diringer (2008) as a possible way forward. All major emitters (developed and developing) would commit to reducing greenhouse gas (GHG) emissions, but they would have the flexibility to devise their own approaches (whether economy-wide targets, efficiency standards, efforts towards renewable energy, curbing deforestation, and so forth).1 Many developing countries are concerned and sceptical about the prospect of new regulatory arrangements. They do not wish to become "rule-takers" in yet another sphere of global politics which leaves them vulnerable to rules, monitoring, and enforcement which they see as having asymmetric impact to their disadvantage. We focus on: the participation of developing countries in rule-making, and the monitoring, verification, and enforcement processes. As mentioned above, developing countries are concerned that a small group of powerful, industrialized countries will mostly "do" the regulating, leaving them highly constrained, but marginalized, with little influence or control over the rules and their application. Below we draw out why developing countries might be concerned and what kinds of arrangements might reduce the risk that they will be marginalized from arrangements.
Keywords: 330; Klimawandel; Umweltpolitik; Global Governance; Welt